Analisis Unsur-Unsur Tasybih Pada Mahall al-Qiyam Dalam Kitab Al-Barzanji Karya Syekh Ja’far Al-Barzanji - Siti Nurhalisa (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2024)
The book Al-Barzanji is a literary work that narrates the life of Prophet Muhammad (peace be upon him) from before his birth to his passing. The work begins with praise from the author towards Prophet Muhammad (peace be upon him), as recorded at the outset with the word